Mosby's respiratory care equipment - Cairo, Jimmy M. (St. Louis, MO : Elsevier, 2022)
Stay ahead of the curve with this clinically relevant text with in-depth details on the latest respiratory devices and equipment divided into clearly defined sections with thorough and systematic descriptions of ventilators, transport, home-care, neonatal & pediatric ventilators, and alternative ventilators. Provides information used by respiratory therapists in all areas of practice including neonates and pediatrics, cardiovascular diagnostics, and the growing field of sleep medicine. Chapters combine theory with the latest advances in new devices and techniques, computer-assisted technologies, pharmacological agents, and clinical practice guidelines. Explains the mechanics of the equipment while maintaining a focus on the clinical applications and includes a focus on specific ventilator characteristics such as selecting modes, setting parameters, monitors and displays, alarms and indicators, graphics, special features, and troubleshooting for lesser-used ventilators. This how-to approach prepares students to work within the entire spectrum of respiratory care
SECTION I: Introduction - 1. Basic physics for the respiratory therapist ; 2. Principles of infection control -- SECTION II: Medical Gases - 3. Manufacture, storage, and transport of medical gases ; 4. Administering medical gases: Regulators, flowmeters, and controlling devices -- SECTION III: Airway Management - 5. Airway management devices and advanced cardiac life support ; 6. Humidity and aerosol therapy ; 7. Lung expansion therapy devices -- SECTION IV: Assessment - 8. Assessment of pulmonary function ; 9. Assessment of cardiovascular function ; 10. Blood gas monitoring ; 11. Sleep diagnostics -- SECTION V: Critical Care and Extended Care Devices - 12. Introduction to ventilators ; 13. Mechanical ventilators: General use ventilators: Adult, pediatric, and neonatal critical care devices ; 14. Transport, home care, and noninvasive ventilatory devices ; 15. Special techniques in respiratory care patient management -- Appendix A: Suggested Answer Key for Clinical Scenarios -- Appendix B: Answer Key for Chapter Assessment Questions -- Appendix C: Normal Reference Ranges -- Appendix D: Frequently Used Formulae and Values -- Glossary -- Index
Includes bibliographical references and index
Keywords: Respiratory therapy -- Equipment and supplies; Respiratory intensive care -- Equipment and supplies